Sustainable Touristic Development in Rural Areas: The Issue of Carrying Capacity, and Systems Theory - Nicolopoulos Philippos (Journal of Sociocybernetics, 2022)
The mass conventional tourism, mainly appeared in coastal areas of southern countries with mild weather and warm summer in the last 50-60 years, had negative impacts on the natural environment and on local cultures. This kind of tourism gave priority to the increase of economic profit of local societies “selling” natural advantages to people who liked summer vacation “relax”. On the contrary in the last years, exactly because of the aforementioned negative impacts, there exists a tendency for a sustainable touristic development, connected with the so-called alternative and qualitative tourism. This is another kind of tourism which intends to combine the meeting of the desires of tourists, the reinforcement of local and national economy of countries and the non-degradation of natural and cultural capital of the touristic areas. That’s why it began to turn to other activities which are more “qualitative” and to consider the protection of natural environment as an issue of first priority. From this point of view the rural areas, exactly, because many times are more “virgin” and “exciting” compared with the crowded coastal zones are preferable. In the present article I propose how systems theory and sociocybernetics can contribute to the sustainable development of this kind, based on an “intelligent” control system which applies their principles and their perspective.